Art And Visual Arts - Čolakov, Nevena D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
The aim of this theoretical paper is to direct us towards deliberation of the connection between Visual Arts teaching, and the notion of arts. At the beginning, we will try to define the term of art as a specific phenomenon and perceive art through various theories, among which are the sociological aspect, instrumental theories, naturalistic, formalistic and formal-semantic art theories. Through a brief presentation of historical development of Visual Arts teaching, we will show the function of art in pedagogical theory and educational praxis. The school, as the centre of pedagogical praxis, is one of the most important mediators between creativity and understanding of the creation, so we try to shape the art consciousness of students through Visual Arts education. The essence of art is in its vitality and humanism and the art has its place in the life of society. Visual Art teaching is, among other things, a subject that should set the correct aesthetic orientation, separating what is valuable from what is not.